Predicting Optimal Tariff of Indonesia’s Carbon Tax: A Reflection on Japan and Singapore - Iqbal, Syaiful; Diana , Shelly (Universitas Pendidikan Ganesha, 2024)
This study aims to predict the optimal carbon tax rate in Indonesia through a reflection on the experiences of Singapore and Japan, so it does not cause carbon leakage. This study uses a qualitative descriptive approach to explain the mechanism of determining carbon tax policies in a country along with the amount of the rate. The quantitative and qualitative data involved in this study are collected from policy documents, official government reports, and scientific articles on carbon taxes in Japan, Singapore, and Indonesia. This study argues that the carbon tax rate in Indonesia is lower than Japan and Singapore. Japan applies a tax rate of USD 2.65/tCO2, Singapore sets a tax rate of USD 18/tCO2, while Indonesia applies a minimum of USD 1.88/tCO2. These differences can trigger carbon leakage in Indonesia. The analysis results the carbon tax tariff in Indonesia optimally is IDR 300,000/tCO2. This tariff provides a policy recommendations to overcome the limitations of carbon tax policies in Indonesia.